Pentecostal Lyrical Theology in Dialogue with Lutherans on Water Baptism - Baker, Josiah (PentecoStudies, 2022)
Lutheran-Pentecostal dialogue has devoted significant attention to water baptism. Much of this reflection, however, has been encumbered by a lack of developed scholarly attention given to baptism among Pentecostals. Pentecostal language of ordinance and symbolism has even led Lutherans to critique Pentecostal baptismal theology as anthropocentric and anaemic. To correct this misunderstanding, I study a Pentecostal baptismal hymn - Brooke and Scott Ligertwood’s "Beneath the Waters (I Will Rise)" - as an alternative entry point into Pentecostal baptismal theology. The analysis demonstrates that the testimonial dimension of baptism presumes a recognition of divine work in the rite. The baptizand encounters Christ and is brought into a deeper participation in his death and resurrection. This understanding of Pentecostal baptismal theology advances dialogue with Lutherans by clarifying Pentecostal rhetoric and revealing more insightful questions into the tensions between the two traditions.